Physicochemical mechanisms of polyethyleneimine-grafted graphene oxide in shale swelling mitigation through nanocomposite-clay interaction analysis - Abdul Hazim Abdullah; Syahrir Ridha; Dzeti Farhah Mohshim; Mohd Azuwan Maoinser (Discover Materials)
Abstract Efficient inhibition of water-sensitive clays is vital for improving drilling operations and mitigating shale instability. The application of nanomaterials to enhance shale stability has been constrained by uncertainties related to their mechanisms of shale stability. These challenges arise from lack of investigation into shale-nanoparticle interaction forces. This study investigates the physicochemical mechanisms of polyethyleneimine-grafted graphene oxide (PEI-GO) nanocomposites in mitigating shale swelling through detailed analysis of nanocomposite–clay interactions. Advanced characterization techniques, including Raman spectroscopy, x-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and transmission electron microscopy (TEM), confirmed the successful synthesis of PEI-GO. Linear swelling tests demonstrated that 0.3 wt% PEI-GO effectively reduced shale swelling compared to other concentrations, as well as conventional inhibitors like KCl and PEI. D-spacing measurements and microstructural imaging revealed that PEI-GO intercalates into clay layers, decreases d-spacing, and modifies surface interactions, thereby reducing shale swelling. The Derjaguin-Landau-Verwey-Overbeek (DLVO) model, incorporating attractive van der Waals forces and repulsive electrostatic double-layer interactions, was utilized to quantify the interaction energies between PEI-GO and clay minerals through measured zeta potentials and particle size. Zeta potential analysis and DLVO modelling highlighted the stabilization mechanism, where PEI-GO neutralizes surface charges, enhances adsorption, and forms electrostatic and hydrogen bonds to repel water from interlayers. The findings establish the dual functionality of PEI-GO as a physical and chemical stabilizer, offering a sustainable solution for shale stability in water-based drilling fluids. This study advances the understanding of clay-water interactions and provides insights for designing high-performance nanocomposite materials for challenging drilling environments.